HIPOGRAM DALAM PUISI SAJAK LIAR DI MEDIA SOSIAL INSTAGRAM: TINJAUAN SEMIOTIKA RIFATERRE - Almuminin, Fitri; Mayong, Mayong; Saguni, Suarni Syam (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
Hypograms in Sajak Liar Poetry on Social Media Instagram: Overview of Rifaterre Semiotics. This study aims to describe the data that includes the potential and actual hypograms, in other words, to describe the origin of the texts in several poems in the Sajak Liar poetry account. This type of research is descriptive qualitative research. The results of the research on Sajak Liar poetry show that there are several circumstances behind the writing of the selected work as well as different implications of several lines of several poems that show actual evidence of the poetry. This type of research is descriptive qualitative research. The results of the research on wild poetry show that there are several circumstances behind the writing of the selected work as well as different implications of several lines of several poems that show actual evidence of the poetry.